2020
DOI: 10.1097/sla.0000000000004052
|View full text |Cite
|
Sign up to set email alerts
|

Increased Intraoperative Faculty Entrustment and Resident Entrustability Does Not Compromise Patient Outcomes After General Surgery Procedures

Abstract: Background: Intraoperative resident autonomy has been compromised secondary to expectations for increased supervision without defined parameters for safe progressive independence, diffusion of training experience, and more to learn with less time. Surgical residents who are insufficiently entrusted during training attain less autonomy, confidence, and even clinical competency, potentially affecting future patient outcomes. Objective: To determine if OpTrust, an educational intervention for increasing intraoper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…Faculty are often challenged with trying to balance the dual responsibility of education and patient care through the medium of the trainee . However, appropriate entrustment allows satisfactory care to be provided to the patient at hand while also allowing the resident to develop competence, ultimately benefiting the patients they will one day go on to care for independently . In the new surgical education model incorporating entrustable professional activities, faculty entrustment will become an even greater driver of resident progression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Faculty are often challenged with trying to balance the dual responsibility of education and patient care through the medium of the trainee . However, appropriate entrustment allows satisfactory care to be provided to the patient at hand while also allowing the resident to develop competence, ultimately benefiting the patients they will one day go on to care for independently . In the new surgical education model incorporating entrustable professional activities, faculty entrustment will become an even greater driver of resident progression.…”
Section: Discussionmentioning
confidence: 99%
“…OpTrust allows for the assessment of both intraoperative faculty entrustment and resident entrustability behaviors in real time and acknowledges the relationship between the educator and learner during these interactions . Previous studies have demonstrated that increased resident entrustablity advances resident autonomy, does not compromise postoperative patient outcomes, and is associated with progression through milestones . Importantly, faculty entrustment has shown to be a key factor in how residents exhibit entrustability, and faculty surgeons who demonstrate progressive intraoperative entrustment can help propel resident autonomy forward .…”
Section: Introductionmentioning
confidence: 99%
“…OpTrust, an educational package aimed at improving resident entrustment, is one such model that has been previously described . Analyzing their experience with this intervention, Williams and colleagues reported no difference in outcomes between historical controls and a cohort of more than 8000 patients who underwent surgery after implementation of OpTrust. These authors concluded that increasing resident entrustment does not worsen patient outcomes, and that a formal educational intervention may encourage increased resident autonomy.…”
mentioning
confidence: 99%
“…As we transition toward a competency-based educational model, continued professional development will help improve opportunities for autonomy. OpTrust, an educational package aimed at improving resident entrustment, is one such model that has been previously described . Analyzing their experience with this intervention, Williams and colleagues reported no difference in outcomes between historical controls and a cohort of more than 8000 patients who underwent surgery after implementation of OpTrust.…”
mentioning
confidence: 99%
“…Enstrustibility to perform independent surgery is the elephant in the room that cannot be accounted for in the registry analysis. Despite competency-based curriculums, training techniques, and multiple objective scales, entrustibility remains a subjective realm that depends on human factors beyond competency alone.…”
mentioning
confidence: 99%